Efeito do teor de CeO2 em catalisadores de Pt/CeO2-Al2O3 para as reações de oxidação parcial e reforma do metano - Santos, Ana Cláudia Sousa Fonseca (2005)
The effect of CeO2 loading in Pt/CeO2-Al2O3 catalysts was investigated. Pt catalysts supported on mixed CeO2-Al2O3 carriers with different CeO2 loading 1, 3, 6, 12, 20 wt.% were prepared by incipient wetness impregnation method. For all samples, the Pt content was about 1 wt.%. The catalysts were characterized by SBET, X-ray diffraction (XRD), temperature-programmed reduction (TPR), UVVis diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS), reaction of dehydrogenation of cyclohexane and oxygen storage capacity (OSC) measurements. SBET results showed that the ceria promoted the stabilization of the superficial area of the alumina in samples of CeO2-Al2O3 with low CeO2 content (≤ 6%). XRD showed the formation of nanocrystallites of ceria on alumina surface when the amount of CeO2 was higher than 6 wt.%. TPR patterns indicated that the presence of Pt promoted the reduction of CeO2 in lower temperature than what was observed for the CeO2-Al2O3 supports. The increase of CeO2 loading lead to an increment in the OSC. The results for the reactions of partial oxidation, steam reforming and autothermal reforming of methane revealed that the activity of Pt/CeO2-Al2O3 catalysts was dependent of the CeO2 loading. Pt catalyst with CeO2 loading higher than 12 wt.% exhibited the highest specific activity and stability for partial oxidation of methane. This high stability was attributed to a combination of the properties as the presence of the CeO2 fluorite structure and different OSC values. Although the superficial structure of Pt did not show a decisive role for the high stability of Pt/CeO2-Al2O3 catalysts with CeO2 loading higher than 12 wt.%, the different Pt morphologies can show different rates for methane activation resulting in a better performance of surface carbon removal and therefore making more Pt sites available to the reaction.